2012
DOI: 10.1016/j.joca.2012.02.452
|View full text |Cite
|
Sign up to set email alerts
|

Cell lines for the human intervertebral disc: nucleus pulposus and annulus fibrosis

Abstract: during the past months. Participants were excluded if they (i) exhibited concomitant pain from other knee structures; (ii) described current or previous physiotherapy for knee pain (prior 12 months); and (iii) knee or hip arthroplasty or osteotomy. Radiographic severity of TFJ OA was assessed from a semiflexed, posteroanterior weight-bearing short film radiograph with the feet externally rotated by 10 . Radiographic severity of PFJ OA was assessed from weight-bearing skyline radiographs, with the knee position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recent progress in identifying phenotypic markers for notochordal [68] and NP [29] cells has revealed that NP cells are derived directly from the notochordal cell population [69]. However, subpopulations of NP [70,71] and AF [72,73] cells with potentially differing ontogenies have been identified in adult IVDs, including those of non-notochordal origin. It is therefore speculated that a small notochordal cell population persists into adulthood, producing ECM that encourages the development of a healthy NP cell phenotype and guards against the onset of early IVD degeneration [74][75][76][77].…”
Section: Ivd Development and Maturationmentioning
confidence: 99%
“…Recent progress in identifying phenotypic markers for notochordal [68] and NP [29] cells has revealed that NP cells are derived directly from the notochordal cell population [69]. However, subpopulations of NP [70,71] and AF [72,73] cells with potentially differing ontogenies have been identified in adult IVDs, including those of non-notochordal origin. It is therefore speculated that a small notochordal cell population persists into adulthood, producing ECM that encourages the development of a healthy NP cell phenotype and guards against the onset of early IVD degeneration [74][75][76][77].…”
Section: Ivd Development and Maturationmentioning
confidence: 99%